New Indonesian Science Curriculum for Junior High School: A Content Analysis to Support STEM SDGs - Greny Mispi Anisa Sari; Vika Yulinda Antika; Remanda Arya Wisutama; Laela Nisfi Syiami; Nurul Fitriyah Sulaeman; Atin Nuryadin; Lambang Subagiyo (Program Studi Pendidikan Fisika, 2022)
Recently, Indonesia has experienced changes in the school curriculum to be more in line with the development of globalization. The 2013 curriculum changed into the